2012
DOI: 10.1186/1742-4690-9-63
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus gag and protease: partners in resistance

Abstract: Human Immunodeficiency Virus (HIV) maturation plays an essential role in the viral life cycle by enabling the generation of mature infectious virus particles through proteolytic processing of the viral Gag and GagPol precursor proteins. An impaired polyprotein processing results in the production of non-infectious virus particles. Consequently, particle maturation is an excellent drug target as exemplified by inhibitors specifically targeting the viral protease (protease inhibitors; PIs) and the experimental c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
177
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
2
2
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 130 publications
(181 citation statements)
references
References 117 publications
(182 reference statements)
3
177
0
1
Order By: Relevance
“…The results presented here advance recent work in the field, using Potts models to study HIV-1 evolution (Barton et al 2016b;Butler et al 2016), by providing systematic prospective predictions quantifying the influence of specific multi-residue patterns on the tolerance of drug resistance mutations. Recent publications have reported that mutations near or distal to Gag cleavage sites play a role in promoting cleavage by drug-resistant and enzymatically deficient proteases, by selecting for mutations that increase substrate contacts with the protease active site, altering the flexibility of the cleavage site vicinity, or by as of yet unknown mechanisms Kolli et al 2009;Breuer et al 2011;Parry et al 2011;Fun et al 2012;Flynn et al 2015). This suggests that viral coevolution of Gag with selective protease mutations may further stabilize multiple resistance mutations; thus, the analysis of protease mutation patterns can be extended to include amino acid substitutions within Gag and the Gag-Pol polyprotein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results presented here advance recent work in the field, using Potts models to study HIV-1 evolution (Barton et al 2016b;Butler et al 2016), by providing systematic prospective predictions quantifying the influence of specific multi-residue patterns on the tolerance of drug resistance mutations. Recent publications have reported that mutations near or distal to Gag cleavage sites play a role in promoting cleavage by drug-resistant and enzymatically deficient proteases, by selecting for mutations that increase substrate contacts with the protease active site, altering the flexibility of the cleavage site vicinity, or by as of yet unknown mechanisms Kolli et al 2009;Breuer et al 2011;Parry et al 2011;Fun et al 2012;Flynn et al 2015). This suggests that viral coevolution of Gag with selective protease mutations may further stabilize multiple resistance mutations; thus, the analysis of protease mutation patterns can be extended to include amino acid substitutions within Gag and the Gag-Pol polyprotein.…”
Section: Discussionmentioning
confidence: 99%
“…It is well understood that major drug resistance mutations in HIV-1 protease destabilize the protease in some way, reducing protein stability or enzymatic activity, which can greatly alter the replicative and transmissive ability, or fitness, of that viral strain (Wang et al 2002;Grenfell et al 2004;Bloom et al 2010;Boucher et al 2016). To compensate for this fitness loss, protease accumulates accessory mutations which have been shown to restore stability or activity (Martinez-Picado et al 1999;Chang and Torbett 2011;Fun et al 2012). But it is unclear how the acquisition and impact of primary and accessory mutations are modulated in the presence of the many different genetic backgrounds observed, especially those present in the complex resistant genotypes that arise under inhibitor therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The converse experiment titrating a threefold excess of unlabeled ΔGag are colored in blue; residues that exhibit large PREs and are associated with drug resistance are depicted as dark blue spheres; those exhibiting large PREs only are shown as light blue spheres. Three residues (Thr186, Met200, and His219) in CA also associated with drug resistance (15,16) are depicted as orange spheres; two of these (Thr186 and His219) give large PREs at low ionic strength (see C ), whereas Met200 is close to the patch of CA residues (residues 192-198) that exhibit large PREs at both high and low ionic strengths.…”
Section: W316amentioning
confidence: 99%
“…A comparison of regions involved in transient Gag-protease encounter complexes with residues associated with drug-resistance mutations (14)(15)(16)(17)28) in Gag and protease is provided in Figs. 2D and 3C, respectively (also see Table S2 for additional details).…”
Section: Correlation Of Sites Of Encounter Complexes With Compensatormentioning
confidence: 99%
See 1 more Smart Citation